Nghiên cứu chế tạo lớp phủ polyuretan nanocompozit clay-ống nano cacbon bền thời tiết - Vũ, Phạm Gia; Oánh, Vũ Kế; Xuân Hằng, Tô Thị; Trúc, Trịnh Anh; Dương, Nguyễn Thùy (Vietnam Journal of Chemistry, 2014)
Surface degradation is a common problem in polymeric coatings when they are exposed to  sunlight moisture and  oxygen. In order to reduce their surface degradation, thus keeping the coatings’ original properties, carbon nanotubes (CNTs) and organic clay nanofil 8 (N8) were added. The Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and Scanning electron microscope (SEM) were performed to analyze the structure of nanocomposite coatings. The mechanical properties, gloss and structure of nanocomposite coatings are evaluated before and after exposure to UV light and moist heat for various lengths of time. Test results also showed that UV exposure along with  salt fogging reduced the coating mechanical properties and surface cracking of the coatings. These results clearly indicate that N8 and CNTs added to polyurethane coatings reduce UV degradation, lessen surface cracks and mechanical properties. Keywords: Carbon nanotube, clay, paint, nano coating, polyurethane, polymer nanocompsite.